(untitled) (Письма в ЭЧАЯ, 2024)
Indirect experimental angular distributions data for protons elastically scattered from 14N target nuclei at low energies: 1.8, 2.2, 3.0, 3.3, and 3.8 MeV are extracted from the available experimental excitation functions for p + 14N. These extracted data are subjected to theoretical analysis within the framework of single folding optical potential (SFOP) model in order to obtain the optimal potential that could fairly reproduce the p + 14N elastic scattering angular distributions. The obtained potential parameters are then used to calculate the astrophysical S-factor for 14N(p,γ)15O radiative capture reaction at very low energies where no experimental data is available and compared with the available experimental data.